Information, Belief Elicitation and Threshold Effects in the 5X1000 Tax Scheme: A Framed Field Experiment - Leonardo Becchetti; Vittorio Pelligra; Tommaso Reggiani (Institute of Labor Economics (IZA), 2017)
In this paper we study by means of a framed field experiment on a representative sample of the population the effect on people's charitable giving of three, substantial and procedural, elements: information provision, belief elicitation and threshold on distribution. We frame this investigation within the 5X1000 tax scheme, a mechanism through which Italian taxpayers may choose to give a small proportion (0.5%) of their income tax to a voluntary organization to fund its activities. We find two main results: a social information effect, since information on total donations received by the organizations in the previous year significantly increases the share of donors, and a distributional effect, leading, the information provision, to a significant increase in the share of donors to the organization reporting the lowest aggregate donations.
Keywords: C91; D64; H00; 330; charitable-giving; framed field experiment; social information effect; 5X1000